1984
DOI: 10.21273/hortsci.19.2.254
|View full text |Cite
|
Sign up to set email alerts
|

‘Pitoma Slanopadja’, a Natural Pear Hybrid Between Pyrus amygdaliformis and P. communis

Abstract: The effect of external factors on the rooting of hardwood cuttings of the ‘Gisela 5’ cherry rootstock (Prunus cerasus × Prunus canescens) was studied. Experiments were conducted with cuttings of different lengths (15, 20, 25, and 30 cm) and diameters (6 to 8, 9 to 11, and 12 to 14 mm) and with different indole-3-butyric acid (IBA) concentrations (0, 1, 2, 3, 4, and 6 g·L−1). Significantly improved rooting was achieved using cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Vermiculite has also been found to positively affect the rooting of Iranian cultivars of olive when used as a medium component for cuttings grown under fog conditions (Hosseini et al, 2004). Exadaktylou et al (2009) found that perlite in combination of peat (total porosity 70 %, water holding capacity 30 %) and perlite (total porosity 75 %, water holding capacity 20 %) are suitable for rooting in hardwood cuttings of cherry cultivar 'Gisela 5'. Tofanelli et al (2003) found that the highest rooting percentage was recorded in vermiculite substrate when six rooting substrates i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Vermiculite has also been found to positively affect the rooting of Iranian cultivars of olive when used as a medium component for cuttings grown under fog conditions (Hosseini et al, 2004). Exadaktylou et al (2009) found that perlite in combination of peat (total porosity 70 %, water holding capacity 30 %) and perlite (total porosity 75 %, water holding capacity 20 %) are suitable for rooting in hardwood cuttings of cherry cultivar 'Gisela 5'. Tofanelli et al (2003) found that the highest rooting percentage was recorded in vermiculite substrate when six rooting substrates i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The 'Gisela 5' sweet cherry rootstock is propagated with greenwood, soft or hardwood cuttings (Exadaktylou et al 2009), but also micropropagation has been reported (Ružić et al 2000;Nacheva & Gercheva 2009;Bošnjak et al 2012;Clapa et al 2013;Šiško 2011. An efficiency in tissue culture propagation is strongly influenced by a mineral composition of culture medium and its interaction with other medium compounds, as water quality, sugars, growth regulators, vitamins, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, IBA is commercially accepted as an exogenous rooting hormone for many plant species because of its high root-inducing capacity and light stability (Pacurar et al, 2014). The optimal auxin dose for rooting varies between species and genotypes (Exadaktylou et al, 2009;Luwig-M€ uller et al, 2005;Rosier et al, 2004). IBA can be used alone or in combination with other auxins such as NAA, depending on the specific condition, to achieve better rooting performance (Cano et al, 2014).…”
mentioning
confidence: 99%